ANALISIS EFEKTIVITAS PELAKSANAAN PROGRAM KELUARGA HARAPAN 2011 (HE ANALYSIS OF 2011 FAMILY HOPE PROGRAM IMPLEMENTATION EFECTIVITY) - Samosir, Agunan P. (Jurnal Borneo Administrator, 2013)
Government targets to reduce poverty is a substantial problem. Various programs have been implemented, but the result is not so satisfactory. Since 2007, the government accomodates a more transparent and accountable poverty reduction programs than the countries that successfully implement them . The program is known as the family hope program or conditional cash transfer ( CCT ). CCT had been evaluated several times in 2009 - 2010 altogether  by the Ministry of Social Affairs, SMERU and Bappenas Institute . The results were quite surprising and provided concrete recommendations on improving CCT. In 2011, the Fiscal Policy Office, the Ministry of Finance ( MoF ) conducted field surveys to evaluate the effectiveness of CCT implementation in eight beneficiary areas of social assistance programs . The program is effective to reduce poverty and deserves to be continued in the coming year to improve the administration activities, target , expansion of CCT beneficiaries, CCT companionquality and CCT monitoring and evaluation mechanism.Keywords: CCT , social assistance , extremely poor households , the state budgetTarget Pemerintah untuk menurunkan tingkat kemiskinan merupakan masalah yang cukup berat. Berbagai program telah dilaksanakan, tetapi hasilnya belum begitu memuaskan. Sejak tahun 2007, Pemerintah mengakomodir program penurunan kemiskinan yang lebih transparan dan akuntabel dari negara-negara yang berhasil melaksanakannya. Program tersebut dikenal dengan program keluarga harapan (PKH) atau cash conditional transfer (CCT). PKH telah beberapa kali dievaluasi tahun 2009 - 2010 secara paralel oleh Kementerian Sosial, SMERU dan Bappenas. Hasilnya cukup mengejutkan dan memberikan rekomendasi yang konkrit dalam penyempurnaan PKH. Tahun 2011, Badan Kebijakan Fiskal (BKF), Kementerian Keuangan (Kemenkeu) melakukan survei lapang untuk mengevaluasi pelaksanaan efektivitas PKH di delapan daerah penerima program bantuan sosial. Program ini cukup efektif untuk menurunkan tingkat kemiskinan dan layak untuk dilanjutkan pada tahun mendatang dengan memperbaiki kegiatan administrasi, target sasaran, perluasan daerah penerima PKH, kualitas pendamping PKH dan mekanisme monitoring dan evaluasi PKH.Kata kunci:  PKH, bantuan sosial, rumah tangga sangat miskin, APBN